"The Plane of Y0": Evaluating Reliability of a Novel Method of Measuring the Liver With Sonography Using Internal References. (November 2022) - Joish, Upendra Kumar; Abhishek, S.; Gund, Shardul
Objective: The present methods for the linear measurement of the liver with sonography are based on external reference lines. In addition, these measurements are subject to interrater variability due to relative mobility of liver and abdominal wall during breathing, change in position, and so on. A novel method using a plane with two internal references (plane of Y0) was developed as an alternative. The purpose of this study was to estimate the reliability of the novel method and compare with other commonly used methods. Materials and Methods: A prospective, analytical, cross-sectional study was completed in a radiology department, including individuals referred for sonography and a contrast-enhanced computed tomography (CT) of abdomen. Three radiologists sonographically measured the craniocaudal dimension of liver in the "plane of Y0, " midclavicular, and anterior axillary lines for each participant. In 60 participants, the craniocaudal measurements obtained in the "plane of Y0, " in both contrast-enhanced CT and sonography, were compared for validity. Interrater correlation coefficients were calculated for each method. Results: Three hundred thirty-four participants underwent sonography of the liver. Sixty of them also underwent a contrast-enhanced CT. The craniocaudal measurements within the "plane of Y0" showed excellent reliability in comparison with other methods. It was found to be valid when compared with measurements completed on the CT image. Conclusion: Measuring the liver in the "plane of Y0, " with two identifiable internal references, is reliable, valid, and recommended for possible use in daily clinical practice. Key Takeaways: Using internal reference points for measurements of internal organs, with sonography, will reduce interoperator variability. The "plane of Y0" passing through two internal reference points within the liver, the branching of right portal vein (Y shaped) and gallbladder (0 shaped lumen), can be easily acquired with sonography. Measurement in the craniocaudal dimension of liver, in the "plane of Y0, " showed validity and high interrater reliability (0.91). The normal range of measurements in adults was found to be 10.5 to 15.1 cm.